Transient elastography is the best-performing non-invasive test of liver fibrosis in obese Asian patients with non-alcoholic fatty liver disease: a pilot, cross-sectional study - Kaliyaperumal, Kalaiyarasi (2024)
Background and Objectives: The prevalence of NAFLD (non-alcoholic fatty liver disease) is increasing, and up to 64% of Asian patients with NAFLD are obese. Non-invasive tests (NITs) for the assessment of liver fibrosis are increasingly being used, but data on their performance in obese Asian patients are lacking. In this pilot cross-sectional study, we aim to compare the distribution of serum and radiological markers of fibrosis between obese Asian biopsy-proven NAFLD patients with and without fibrosis and estimate the diagnostic accuracies of these indices. Materials and Methods: Obese Asian patients with NAFLD and who had undergone a liver biopsy showing histological evidence of NAFLD were invited to participate. Liver fibrosis was assessed using laboratory (APRI, AAR, BARD, FIB4, NFS, and Asia-Pacific NAFLD advanced fibrosis score) and imaging modalities (TE: transient elastography, MRE: magnetic resonance elastography, and SWU: shear wave ultrasonography). Results: A total of 16 patients were included in the final analysis. On liver biopsy, nine patients (56.3%) had significant fibrosis (F2 or higher), and six of these patients had advanced fibrosis (F3 or higher). F4 fibrosis was present in one patient (6.3%). For the laboratory markers, we found that the BARD score correctly identified five out of six patients with advanced fibrosis (83.4%, p value 0.045). Among all the NITs studied, liver stiffness measured by TE had the highest accuracy of 87.5% in its established threshold of 8.5 kPa for the detection of advanced fibrosis. MRE also performed well (81.2% in 3.64 kPa). Conclusions: In conclusion, TE has performed well in the detection of advanced fibrosis in obese Asian patients with biopsy-proven NAFLD in our pilot study. Further large-scale definitive studies are needed to validate the results of our findings.